Failure of Synthetic Implants: Strategies and Management - Jang, Yong Ju; Kim, Shin Ae; Alharethy, Sami (Facial Plastic Surgery, 2018)
Dorsal augmentation with synthetic implants is the most commonly performed rhinoplasty procedure, especially in the East-Asian region. However, as in all other surgical procedures, complications are inevitable. Complications that need to be managed surgically include displacement, deviation, suboptimal aesthetic outcome, extrusion, inflammation, infection, and changes in skin quality. Most complications can be easily managed with revision surgery. After the removal of the synthetic implant from the nasal dorsum, different dorsal implant materials such as dermofat, alloderm, or fascia-wrapped diced cartilage, conchal cartilage with perichondrial attachment, and costal cartilage are preferred. An irreversible change in the skin/soft tissue envelope poses a challenge that usually requires reconstructive surgery with a local flap. Therefore, early detection and prompt management of the complication are essential for minimizing the severity of the deformity and the complexity of the surgical procedures.
Keywords: rhinoplasty; silicones; Polytetrafluoroethylene; revision surgery